Inter-disciplinary teaching strategies for mental health law. (March 2015) - Hanson, Lynne; Fitzpatrick, Renee; Ella, Shaimaa Abo-El
Abstract: The use of an inter-disciplinary teaching strategy in the context of mental health law is explored here as a means of balancing concerns for the patient's best interests and maximizing their autonomy. One law professor and one psychiatrist participated in joint teaching sessions in the Queen's University School of Medicine, and share their strategies for overcoming perceived conflicts between patient's legal rights and the practice of psychiatry.